THE SPECTRUM OF RADIOLOGICAL FINDINGS IN PATIENTS PRESENTING WITH DIFFERENT CLINICAL INDICATIONS FOR CRANIAL COMPUTED TOMOGRAPHIC SCAN - Ihsan, Hussain Rashid; Ahmad, Salman; Ayaz, Saeed Bin (Pakistan Armed Forces Medical Journal, 2019)
Objectives:To identify the main reasons for seeking computed tomography (CT) scan evaluation and primary brain and skull pathologies seen on CT scan and to determine the percentage of negative and positive CT scans for a particular referring reason and correlate the commonest reason for seeking CT scan evaluation with age and gender.Study Design:A cross-sectional study.Place and Duration of Study: Department of Radiology, Sheikh Khalifa Bin Zaid Al Nahyan Hospital Muzaffarabad, Azad Jammu and Kashmir, from Jan to Sep 2016.Material and Methods:Through consecutive sampling, we included 137 patients referred for radiological evaluation of skull and brain through CT scan. The study was performed by a senior CT scan technologist using CT scan machine Brilliance CT 16 slice – DS, taking 0.5 mm slices in all patients and reviewed by a consultant radiologist. The sample was divided into two age-groups i.e. age ≤36 years and age >36 years. The data were analysed using statistical program Statistical Package for Social Sciences version 20.0.Results:Out of 137 individuals, (mean age: 34 ± 23 years), 86 (62.8%) were male and 51 (37.2) were female. The majority (61.3%, n=84) of the individuals were referred for complaint of head trauma. The head trauma was significantly more common in age group of ≤36 years (p